2013
DOI: 10.1037/a0034686
|View full text |Cite
|
Sign up to set email alerts
|

Immediate response strategy and shift to place strategy in submerged T-maze.

Abstract: A considerable amount of research has demonstrated that animals can use different strategies when learning about, and navigating within, their environment. Since the influential research of Packard and McGaugh (1996), it has been widely accepted that, early in learning, rats use a flexible dorsal hippocampal-dependent place strategy. As learning progresses, they switch to a less effortful and more automatic dorsolateral caudate-dependent response strategy. However, supporting literature is dominated by the use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
17
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 20 publications
3
17
0
1
Order By: Relevance
“…Across the interspersed probe tests, we observed the behavioral pattern expected on the basis of Asem and Holland’s (2013) findings, with rats switching from response learning to place learning. However, this pattern was not affected by lidocaine infusions.…”
Section: Methodssupporting
confidence: 57%
See 3 more Smart Citations
“…Across the interspersed probe tests, we observed the behavioral pattern expected on the basis of Asem and Holland’s (2013) findings, with rats switching from response learning to place learning. However, this pattern was not affected by lidocaine infusions.…”
Section: Methodssupporting
confidence: 57%
“…However, in the submerged T-maze, we observed the opposite behavioral pattern—rats initially used a response strategy and gradually switched to a place strategy (Asem & Holland, 2013). Due to a complete inversion of previous behavioral results, the underlying neural circuitry and the characterization of strategy shifts over training in the submerged T-maze warrants investigation.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Prior research reports have noted differences in shifts in navigation strategy and disruption of behavior as a result of disorientation between dry land and water tasks. One recent study using a T maze found that rats demonstrated an initial response strategy that shifted to place navigation after multiple days of training [23], in contrast to findings in the MWT [22]. Other reports have noted that disorienting rats by rotating holding cages prior to training resulted in impaired navigation in a radial arm maze, but not the MWT [24, 25], even when the task was simplified by using a T maze [26].…”
Section: Methodsmentioning
confidence: 99%